Laparotomic vs. laparoscopic myomectomy: surgical outcomes from a tertiary center retrospective study - Efe Çamili, Figen; Bozhüyük Şahin, Tuba; Tolu Cenk, Ezgi; Afşar, Selim; Güney, Gürhan; İslimye Taşkın, Mine (Frontiers in Surgery, 2026)
ObjectiveThis study aimed to retrospectively analyze myomectomy cases performed in our clinic using laparotomic and laparoscopic techniques, and to compare the effects of both surgical approaches on various clinical and surgical outcomes.Materials and methodsPatient records of myomectomy operations performed between 2015 and 2025 at the Department of Obstetrics and Gynecology, Balıkesir University Faculty of Medicine, were reviewed. A total of 213 patients were included, comprising 140 laparoscopic and 73 laparotomic cases. The data such as patient age, number and size of removed myomas, preoperative and postoperative hemoglobin levels, postoperative additional analgesic requirements, length of hospital stay and complication rates will be analyzed to evaluate the advantages of each method in terms of patient comfort and surgical efficacy.ResultsThe mean age of patients undergoing laparoscopic myomectomy was significantly higher than those in the laparotomic group (p < 0.001). The laparoscopic group demonstrated a significantly shorter hospital stay compared to the laparotomic group (p < 0.001). Preoperative and postoperative hemoglobin levels did not differ significantly between the groups. The number of removed myomas was similar; however, the mean myoma diameter was significantly larger in the laparotomic group (p < 0.001). Postoperative opioid use was significantly higher in the laparotomic group (p = 0.01). Larger and more numerous myomas were independently associated with a higher likelihood of laparotomy over laparoscopy (p < 0.001). Among laparoscopic cases, only four required conversion to laparotomy (%2,9) and a single bladder injury was observed.ConclusionLaparoscopic myomectomy provides considerable advantages over laparotomic myomectomy, including reduced hospital stay and lower postoperative analgesic requirements. While laparotomy remains preferable for larger myomas, laparoscopic approaches yield comparable outcomes in terms of hemoglobin levels and complication rates. With appropriate patient selection, laparoscopic myomectomy is a preferred surgical method due to its positive impact on patient recovery, comfort and overall surgical efficacy.